1989
DOI: 10.1177/00220345890680120801
|View full text |Cite
|
Sign up to set email alerts
|

Visual and Instrumental Colorimetric Assessments of Small Color Differences on Translucent Dental Porcelain

Abstract: The CIELAB colorimetric system was used for the study of the relationship between measured color difference values and human observer responses. This study verified that a specific, visually meaningful and precise relationship exists between the magnitude and direction of the measurements and the average dental-observer responses. The results support the use of this system in dentistry as a means of evaluating color by differences. The further development of such systems for clinical use would be warranted and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
270
1
20

Year Published

2004
2004
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 405 publications
(300 citation statements)
references
References 7 publications
9
270
1
20
Order By: Relevance
“…This variation is probably connected with the variability in human eye appreciation of color differences and in experimental conditions of comparison between instrumental and visual evaluation of color differences. Moreover, Seghi et al 17 , in a laboratory study on dental ceramics reported that under ideal conditions of illumination and viewing, a value of ∆E<1 was seldom distinguished by the majority of the observers. Based on this data, we divided the limit of the visual correlation of the results in three categories.…”
Section: Discussionmentioning
confidence: 99%
“…This variation is probably connected with the variability in human eye appreciation of color differences and in experimental conditions of comparison between instrumental and visual evaluation of color differences. Moreover, Seghi et al 17 , in a laboratory study on dental ceramics reported that under ideal conditions of illumination and viewing, a value of ∆E<1 was seldom distinguished by the majority of the observers. Based on this data, we divided the limit of the visual correlation of the results in three categories.…”
Section: Discussionmentioning
confidence: 99%
“…To test whether uniformity of shade tabs of the same grade were acceptable, and whether color difference of adjacent shade grades could be easily differentiated by visual judgments, we had quantitatively measured 5 sets of shade guide by instrumental colorimetry. In 1976, the CIE recommended an approach to a uniform color space, known as CIELAB, and Seghi et al 27 supported the use of the CIELAB system as a means of evaluating color by differences in the field of dentistry. Seghi et al 27 also concluded that 1 DE unit appeared to be a good estimate for the upper limit of the visual threshold or detectable level of the dental observer group under nearly ideal viewing conditions.…”
Section: Discussionmentioning
confidence: 99%
“…In 1976, the CIE recommended an approach to a uniform color space, known as CIELAB, and Seghi et al 27 supported the use of the CIELAB system as a means of evaluating color by differences in the field of dentistry. Seghi et al 27 also concluded that 1 DE unit appeared to be a good estimate for the upper limit of the visual threshold or detectable level of the dental observer group under nearly ideal viewing conditions. Under intraoral conditions the limit to clinical acceptability will be in the range of $2.8-3.7 DE units.…”
Section: Discussionmentioning
confidence: 99%
“…Color difference or ΔE (Eq. (5)) is defined by the following equation [13]: ΔE = ΔL *2 + Δa *2 + Δb *2 (5) where ΔL*, Δa* and Δb* are the respective difference between the measured and predicted CIE LAB values of the shade tabs.…”
Section: Accuracy Of the Calibration Modelsmentioning
confidence: 99%
“…The magnitude of perceptible and/or acceptable color difference for human observers is still not well-defined, nor ideally measured in dental color research. Perceptible color differences range from a ΔE of 1 [4] and 2 [5] in in-vitro studies to 3.7 in an in-vivo study [6]; while acceptable color differences can range from a ΔE of 2.72 [7] and 3.3 [8] for in-vitro studies to 6.8 in an in-vivo study [6].…”
Section: Introductionmentioning
confidence: 99%